Social roles, human capital, and the intrahousehold division of labor: evidence from Pakistan - Fafchamps, Marcel; Quisumbing, Agnes R. (International Food Policy Research Institute, 1999)
Using detailed data from rural Pakistan, this paper investigates whether human capital, learning by doing, gender, and one's status within the family affect the division of labor within households. Results suggest the presence of returns to individual specialization in all farm, nonfarm, and home-based activities. The intrahousehold division of labor is influenced by comparative advantage, based on human capital and by long-lasting returns to learning by doing, but we also find evidence of a separate effect of gender and family status. Households seem to operate as hierarchies with sexually segregated spheres of activity. The head of household and his or her spouse provide most of the labor within their respective spheres of influence; other members work less. When present in the household, daughters-in-law work systematically harder than daughters of comparable age, build, and education. Other findings of interest are that there are increasing returns to scale in most household chores, that larger households work more off-farm, and that better educated individuals enjoy more leisure.